Meshfree Methods for Partial Differential Equations III - Griebel, Michael; Schweitzer, Marc Alexander (Lecture Notes in Computational Science and Engineering, 2007)
Meshfree methods for the numerical solution of partial differential equations are becoming more and more mainstream in many areas of applications. Their flexiblity and wide applicability are attracting engineers, scientists, and mathematicians to this very dynamic research area. This volume represents the state of the art in meshfree methods. It consists of articles which address the different meshfree techniques, their mathematical properties and their application in applied mathematics, physics and engineering.